Clinical effects of Spirulina supplementation on hemoglobin levels in anemic pregnant women: a systematic review and meta-analysis - Budi Gunawan, Made Favian; Soetomo, Cindy Thiovany; Darmayasa, Putu Bagus; Paramyta, I Gusti Ayu Cintya; Jayakusuma, I Putu Prabawa; Gunawan, I Made Indera (Published by Universitas Gadjah Mada, 2026)
Anemia during pregnancy continues to pose a significant burden, particularly in low- and middle-income countries (LMICs). Anemia is a major contributor in increasing maternal illness and negative pregnancy outcomes. Spirulina, a nutrient-dense blue-green alga rich in bioavailable iron, has gained attention as a potential nutritional intervention to support hemoglobin improvement in pregnancy. This systematic review and meta-analysis, adhering to PRISMA standards, sought to assess the impact of Spirulina supplementation on improving hemoglobin levels among pregnant women. A single-arm meta-analysis was performed to assess the change in hemoglobin levels before and after Spirulina supplementation, while a comparative meta-analysis evaluated the mean difference in hemoglobin improvement between Spirulina and standard iron supplementation. Four eligible studies involving 1,070 pregnant women were included. The single-arm analysis demonstrated a significant increase in hemoglobin levels following Spirulina supplementation, with a pooled mean difference (MD) of 1.81 g/dL (95% CI: 0.24 - 3.39; p = 0.024). In the comparative analysis, Spirulina showed a non-significant trend toward higher hemoglobin than standard iron, with a pooled MD of 1.45 g/dL (95% CI: –0.22 - 3.13; p = 0.088). Risk of bias was low to moderate, and the overall certainty of evidence was classified as moderate. These findings suggest that Spirulina may be a promising adjunct for improving maternal hemoglobin, particularly in settings where local cultivation and food-based approaches are preferred. Further high-quality randomized trials are recommended to ascertain its clinical efficacy and inform policy on its integration into maternal nutrition programs.